Cephalometric analysis of the middle part of the face in patients with mandibular prognathism - Čutović, Tatjana; Jović, Nebojša; Kozomara, Ružica; Radojičić, Julija; Janošević, Mirjana; Mladenović, Irena; Matijević, Stevo (Vojnosanitetski pregled, 2014)
Background/Aim. The middle part of the face, that is the maxilla, has always been mentioned as a possible etiologic factor of skeletal Class III. However, the importance of the relationship of maxillary retroposition towards the cranial base is still unclear, although it has been examined many times. The aim of this study was to conduct cephalometric analysis of the morphology of maxilla, including the whole middle part of the face in patients with divergent and convergent facial types of mandibular prognathism, as well as to determine differences betweeen them. Methods. Lateral cephalometric teleradiograph images of 90 patients were analyzed at the Dental Clinic of the Military Medical Academy, Belgrade, Serbia. All the patients were male, aged 18–35 years, not previously treated orthodontically. On the basis of dentalskeletal relations of jaws and teeth, the patients were divided into three groups: the group P1 (patients with divergent facial type of mandibular prognathism), P2 (patients with convergent facial type of mandibular pragmathism) and the group E (control group or eugnathic patients). A total of 9 cephalometric parameters related to the middle face were measured and analyzed: the length of the hard palate – SnaSnp, the length of the maxillary corpus – AptmPP, the length of the soft palate, the angle between the hard and soft palate – SnaSnpUt, the angle of inclination of the maxillary alveolar process, the angle of inclination of the upper front teeth, the effective maxillary length – CoA, the posterior maxillary alveolar hyperplasia – U6PP and the angle of maxillary prognathism. Results. The obtained results showed that the CoA, AptmPP and SnaSnp were significally shorter in patients with divergent facial type of mandibular prognathism compared to patients with convergent facial type of the mandibular prognathism and also in both experimental groups of patients compared to the control group. SnaSnp was significantly shorter in patients with divergent facial type of mandibular prognathism compared to the control group, whereas SnaSnp was significantly smaller in patients with convergent facial type of mandibular prognathism compared to the control group. Additionally, there was a pronounced incisor dentoalveolar compensation of skeletal discrepancy in both groups of patients with mandibular prognathism manifested in the form of a significant upper front teeth protrusion, but without significant differences among the groups, while the maxillary retrognathism was present in most patients of both experimental groups. A pronounced UGPP was found only in the patients with divergent type of mandibular prognathism. Conclusion. The maxilla is certainly one of the key factors which contributes to making the diagnosis, but primarily to making a plan for mandibular prognathism treatment. Accurate assessment of the manifestation of abnormality, localization of skeletal problems and understanding of the biological potential are key factors of the stability of the results of surgical-orthodontic treatment of this abnormality.